The effect of the death of Aedes aegypti figure with a papaya flower soup - Rustam Aji; Wirawan Shakty; Sherly Ratih FSA; Rosmawati Rosmawati; Gustomo Yamistada; Jessy Novitasari (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2021)
Aedes aegypti larvae that are not monitored will develop into adult mosquitoes, the Aedes aegypti mosquito, which can cause dengue fever. DHF disease transmission by Aedes aegypti mosquito larvae. The solution is to break the vector life cycle, by killing Aedes aegypti larvae, which have been using fogging, abate powder, which has side effects on the environment. Researchers are looking for a safe and effective natural larvicide solution, because researchers saw the number of papaya plants planted by residents in their yards. Papaya plants contain the enzyme papain, the protease effect of papain can kill Aedes aegypti larvae. This study aims to determine the effect of mortality of aedes aegypti larvae by immersing papaya flowers in water reservoirs. The research location is in Curup Tengah Village, the number of houses surveyed as many as 36 water reservoirs. Observational research, cross sectional study design. Larva survey using the single larva method. Survey data were analyzed using the chi-square test. The results of the Chi-square analysis showed that the value of P = 0.04 <? 0.05. So Ho is rejected and Ha is accepted, it means that there is a statistically significant relationship between papaya flower immersion on the mortality of Aedes aegypti larvae. so that the community plays an active role in eradicating Aedes aegypti larvae, through activities to get used to soaking papaya flowers and pouring them into water reservoirs as needed.